Co-Designing Future-Based Partnership for a University-Affiliated Organization Using a Futuristic Approach - Anne Namatsi Lutomia (Interdisciplinary Journal of Partnership Studies)
This paper explores a futuristic approach to partnerships through the lens of a university-affiliated organization, focusing on how strategic collaborations can address evolving global challenges. By examining current practices and envisioning future dynamics, the paper provides insights into the role of partnerships in fostering sustainable development, particularly in education, agriculture, and governance. Drawing inspiration from systems learning and the cultural concept of reciprocity, the paper underscores the importance of mutual respect, trust, and collaboration in creating impactful, non-domination partnerships. It highlights the contributions of Scientific Animations Without Borders (SAWBO) by showcasing its innovative use of video animations and multilingual content to enhance knowledge dissemination and empower communities worldwide. The discussion integrates futuristic elements including artificial intelligence (AI) and digital platforms, emphasizing their potential to change partnerships by bridging digital divides and fostering inclusive knowledge-sharing. The conclusion offers recommendations for transformative approaches that prioritize sustainability in building partnerships for a more equitable future.